Preimplantation genetic testing: between the private and the public in the era of precision medicine : short communication = Evaluación genética preimplantatoria : entre lo privado y lo público en la era de la medicina de precisión - Lima, Natacha Salomé; Romero, Miguel Adrián; Delvitto, Ailin; Tropea, Ana; Petino Zappala, María Alejandra; Pallitto, Nahuel; Ferretti, Fernando Pérez; Paragis, María Paula (SCT proceedings in interdisciplinary insights and innovations, 2024)
This presentation is part of the Strategic Development Project PDE/6 2023-2024 funded by the Secretariat of Science and Technology of the University of Buenos Aires. The project aimed to produce a technical report addressing the scope and limitations of preimplantation genetic testing (PGT) in Argentina. The experiences, progress and findings of our interdisciplinary team comprising researchers from biological sciences and psychology are discussed here.Two fundamental aspects of the reproductive medicine field were addressed. Firstly, despite the existence of law 26,862/2013 covering assisted reproductive treatments, preimplantation genetic tests remain excluded from the Mandatory Medical Plan, highlighting access limitations. Moreover, challenges arise from the lack of specific regulations on central issues for the development of reproductive treatments, such as the legal status of non-implanted embryos. This particular situation prompted an analysis of the paradigm shift from collective health to precision medicine.Within this framework, our work critically examined the implications of PGT on approaches to knowledge and interventions in living organisms. We explored how PGT shapes notions of uncertainty, control, anticipation and the individualization of pathological conditions, shedding light on evolving forms of subjectivity. Additionally, we scrutinized genetic essentialism and determinism as discourses that either flatten differences or advocate for the "optimization" of life itself